31P MR spectroscopic imaging of the human prostate at 7 T: T1 relaxation times, Nuclear Overhauser Effect, and spectral characterization. Issue 3 (26th March 2014) - Lagemaat, Miriam W.; Maas, Marnix C.; Vos, Eline K.; Bitz, Andreas K.; Orzada, Stephan; Weiland, Elisabeth; van Uden, Mark J.; Kobus, Thiele; Heerschap, Arend; Scheenen, Tom W.J.
<x xml:space="preserve">Abstract</x> Purpose Optimization of phosphorus (31P) MR spectroscopic imaging (MRSI) of the human prostate at 7 T by the evaluation of T1 relaxation times and the Nuclear Overhauser Effect (NOE) of phosphorus‐containing metabolites. Methods Twelve patients with prostate cancer and one healthy volunteer were scanned on a 7 T whole‐body system using a 31P endorectal coil combined with an eight‐channel 1H body array coil. T1 relaxation times were measured using progressive saturation in a two‐dimensional localization sequence. 31P MRSI was performed twice: once without NOE and once with NOE using low‐power continuous wave 1H irradiation to determine NOE enhancements. Results T1 relaxation times of 31P metabolites in the human prostate at 7 T varied between 3.0 and 8.3 s. Positive but variable NOE enhancements were measured for most metabolites. Remarkably, the 31P MR spectra showed two peaks in chemical shift range of inorganic phosphate. Conclusion Knowledge of T1 relaxation times and NOE enhancements enables protocol optimization for 31P MRSI of the prostate at 7 T. With a strongly reduced 31P flip angle (≤ 45°), a 31P MRSI dataset with optimal signal‐to‐noise ratio per unit time can be obtained within 15 minutes. The NOE enhancement can improve fitting accuracy, but its variability requires further investigation. Magn Reson Med 73:909–920, 2015. © 2014 Wiley Periodicals, Inc.